Surface plasmon resonance of nanoshell particles with PMMA-graphene core. Issue 6 (28th October 2014) - Doležel, Ivo; Tarparelli, Richard; Iovine, Renato; La Spada, Luigi; Vegni, Lucio
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to contribute an analytical and numerical study of a new type of nanoshell particles operating in the visible regime. Design/methodology/approach – The structure consists of a core/shell particle, arranged in a planar array configuration, with a polymethyl methacrylate (PMMA)-graphene core and gold thin shell. Findings – By exploiting the proposed analytical model the design of a metamaterial-based sensor, operating in the optical frequency range, for the detection of tissue diseases is shown. Originality/value – Full-wave simulations confirm the capability of the proposed sensor to identify different compounds by refractive index measurement.